Importancia de la vegetación espontánea para la riqueza de visitantes florales en praderas ornamentales - Aguero, J.L.; Torretta, Juan Pablo; Facciuto, Gabriela Rosa; Marrero, Hugo Javier; Bugallo, Veronica Lucia (Asociación Argentina de Horticultura (ASAHo), 2024)
Poster